NEXUS Gains Talk 14: Integrating water storage: First steps in assessment, progress toward incentives - Ebrahim, Girma; Bhatpuria, Dhyey; Rex, William; Lautze, Jonathan F. (CGIAR System Organization, 2023)
This online NEXUS Gains session at Stockholm World Water Week 2023 drilled down into two practical aspects of how integrated water storage can be realized. First, how to measure and incorporate water volumes available in diverse storage types into one planning framework. Second, how to motivate institutional or behavioral changes required to realize integrated storage. This recording was made available by Stockholm International Water Institute (SIWI).